Identificação de miosina-V e anatomia interna dos sistemas reprodutor e nervoso de Melipona scutellaris latreille (Hymenoptera, Apidae) - Silva, Alexandre Coletto da (2000)
Class V myosins are motor proteins conserved, evotatively, from yeasts to vertebrates and belonging to a superfamily, composed of 15 classes. These proteins have the particularity of interacting with Actin and hydrolyzing ATP to perform their functions. Myosins, as well as kinesiuas and dineins, are molecular motors responsible for the transport of organelles and vesicles along actin filaments and microtubules present in the cytoskeleton. The mutations found in Saecharomyces cerevisiae and Mus musculus revealed the role of Myosin-V in intracellular transport. This protein is expressed in several types of cells, being especially abundant in nerve cells (neurons). In insects, the Myosin-V gene was sequenced in Drosophila melanogaster and mutations in this gene can cause embryonic lethality. In this work, the Western Blot and Immunodetection technique with immunopurified antibodies against specific Myosin-V domains and also against the dinein light chain, a protein associated with Myosin-V, was used to investigate the presence of these proteins in the nervous and breeder of a species of Brazilian stingless indigenous bee, popularly known as Uruçu do Nordeste (Melipona scutellaris Latreille). The results obtained were compared between individuals of the worker and queen castes and, also, in the male. In the second part of this work, an anatomical morphometric study of the structures belonging to the tissues mentioned above was carried out. The results were documented by means of photography and digital image processing and subsequently compared intra species and also with the data available in iterature for the genus Apis. With the immunodetection assays it was possible to verify the presence of Myosin-V in the brains of workers, virgin queens and males. Myosin- / was also detected in the reproductive system (ovaries of virgin queens), showing [that its presence is not restricted to non-nervous tissues. In addition, mild dynein adeias associated with Myosin-V were also immunodetected in reproductive and nervous systems. Research like this opens up a series of perspectives on the presence, role and importance of this molecular engine - Myosin-V - contributing to the development of areas such as biochemistry, genetics and oology, as well as enabling the dissemination of M. scutellaris ( as a new model of neurobiology) - species at risk of extinction, due to anthropic action in different plant communities.